THE ADOPTION OF ISLAMIC FINANCE BY CAMEROONIAN SME ENTREPRENEURS: ARE THERE GENDER DISPARITIES? - Haruna, Ali; Kountchou, Armand Mboutchouang; Oumbé, Honoré Tekam; Wirajing, Muhamadu Awal Kindzeka (Bank Indonesia, 2024)
The recent surge in the global asset value of Islamic finance has pushed Cameroonian policymakers to consider this mode of finance as an important element of the national financial inclusion strategy. This study examines the factors that influence the adoption of Islamic finance by SME entrepreneurs on the one hand and gender differences in adoption on the other hand in Cameroon, a non-Muslim-dominated African country. Based on a sample of 1,358 SME entrepreneurs, a simple logistic model is adopted to analyze the determinants of the decision to adopt Islamic finance while the Fairlie decomposition is afterward employed to test for gender disparities vis-a-vis the adoption of this mode of finance. Results of the logistic regression show that the need to abide by the Sharia law, awareness, attitude, intention, location, and gender positively and significantly affect the decision to patronize the Islamic mode of financing by Cameroonian SME entrepreneurs while subjective norms and age exert negative effects. The results of the Fairlie decomposition show that there exists a mean difference of 8% to the disadvantage of female entrepreneurs concerning the adoption of Islamic finance and that this gap is widened by religious motivation, awareness, intention, and location. Policymakers are encouraged to enhance the level of Islamic finance awareness of SME entrepreneurs, and the sharia compliance of Islamic finance institutions by obliging them to operate under the guidance of qualified sharia boards. These policies should be supported by the implementation of accompanying measures, such as the eradication of societal norms that restrict women's ability to use Islamic finance services.